Time and space-resolved experimental investigation of the electron energy distribution function of a helium capacitive discharge at atmospheric pressure. (10th April 2019) - Boisvert, J-S; Montpetit, F; Vidal, F; Margot, J; Stafford, L
Abstract: Using a collisional radiative model coupled with optical emission spectroscopy (OES) of helium n = 3 levels, the electron temperature (T e ) of an atmospheric-pressure capacitively coupled radiofrequency (AP-CCRF) discharge in helium is determined with space and time resolution. When the AP-CCRF discharge is sustained in the mode, T e varies from 0.2 to 7.2 eV. In this case, high values of T e (>5 eV) occur only during a brief instant (<10 ns) in the high-voltage sheath. When the AP-CCRF discharge is sustained in the mode, T e varies from 0.3 to 0.4 eV during the complete cycle. The physical meaning of these electron temperatures are then analyzed by considering possible departure from the Maxwellian electron energy distribution function (EEDF). As a first approximation to non-Maxwellian distribution functions, a two-parameter EEDF was used to fit the OES data. This approach yields an overpopulation of high energy electrons with respect to the Maxwellian form in the mode and the opposite trend in the mode.